Drought and hydrothermal humidity factor as one of the criteria to estimate its intensity degree (literature review) - E. V. Ionova; V. A. Likhovidova; I. A. Lobunskaya (Зерновое хозяйство России, 2020)
The current paper has considered the following issues: determination of the drought phenomenon and its classification (atmospheric, soil and combined), drought harmfulness and spread in the Russian Federation. It has been established that regional droughts have specific features, namely soil or atmospheric, spring, summer or autumn. There has been given a classification by intensity and coverage of territories by droughts (very strong, strong, medium and weak). There has been shown a response of agricultural plants to various types of droughts. The northwestern and southeastern droughts (the second type) negatively affect the plants, as they combine low air humidity and soil with high temperature. There has been given a partial characteristic of the climate of the North Caucasus region (on the example of the Rostov region). The most used indicators of meteorological research are Selyaninov’s hydrothermal humidity factor (HHF) which is the ratio of the amount of precipitation for a period of at least a month to the sum of temperatures above 10 °C for the same period, reduced by 10 times. The classification of humidification zones according to the HHF is as follows: wet (1.6–1.3); slightly arid (1.3–1.0); arid (1.0–0.7); very arid (0.7–0.4); dry (<0.4). The data of the HHF are given on the example of meteorological conditions of the Zernograd district of the Rostov region (the years of 2001–2015). It has been found that in 2001–2015 the hydrothermal humidity factor over the autumn period was 0.13–0.17 (dry) on average, and the HHF of the summer period was 0.28 (dry). During the studied period, the hydrothermal factor during the growing season was 0.78 (dry) on average. Thus, for the period 2001–2015, the conditions for plants growth and development were unfavorable.